STOCK VALUATION AND BUSINESS PERFORMANCE OF PT INDOFOOD CBP SUKSES MAKMUR TBK AMIDST WHEAT PRICE VOLATILITY DURING THE RUSSIA-UKRAINE CRISIS - Arbrianto, Dimas
The Russia-Ukraine Crisis in 2022 had a detrimental impact on the business performance of PT Indofood CBP Sukses Makmur Tbk (ICBP), the largest noodle manufacturer in Indonesia, due to the volatility of wheat prices. During the second quarter, ICBP experienced a 16% increase in net revenue but a significant decline of 40.1% in profit, primarily attributed to rising commodity prices. This negative trend continued in the third quarter, resulting in a substantial decrease of 33.4% in net profit, despite an increase in sales. As a consequence, the stock price of ICBP declined. To assess the company's valuation in this environment, a fundamental analysis incorporating various macroeconomic factors becomes imperative. This study employs external analysis using PESTLE and Porter's five forces frameworks, internal business environment analysis through financial ratio analysis, intrinsic valuation using free cash flow to firm (FCFF), and relative valuation analysis utilizing price-earnings ratio (P/E), enterprise value to earnings before interest, taxes, depreciation, and amortization (EV/EBITDA) ratios, and price to book value ratio (P/BV). As a result, the intrinsic valuation of ICBP indicates a fair stock value of 12,222 Rupiah per share, while the current share price stands at 10,000 Rupiah per share, suggesting an undervaluation of approximately 18.2%. Similarly, the relative valuation analysis reveals that ICBP is undervalued compared to industry peers based on P/E, EV/EBITDA, and P/BV ratios. Considering the results from both valuation methods, it becomes evident that ICBP is currently undervalued, offering a potential opportunity for future appreciation of the company's share price.